A comprehensive ductile damage model for 3D truss structures. (June 2019) - Felipe, Túlio R.C.; Leonel, Edson D.; Haach, Vladimir G.; Beck, André T.
Abstract: In this paper, a comprehensive ductile-damage model is proposed for non-linear analysis of truss structures. The model combines a positional Finite Element formulation, for handling large displacements; with a ductile model, for describing post-yield behavior; with a continuum damage model, for capturing degradation in terms of porosity variation. Porosity is the result of growth and coalescence of microcavities, and is the main phenomenon in mechanical degradation of structural materials. Using the proposed model, damage grows continuously until the critical damage hypothesized by Lemaitre and Desmorat (2005) is reached. The proposed model is shown to provide an excellent fit to stress–strain curves of eight different materials, ranging from softening to hardening behavior. In application to structural concrete, the proposed formulation results in better agreement to experimental results, in comparison to the models of Mazar (1986) and Lee and Fenves (1998). In application to a real 3D truss, the proposed formulation described the exact equilibrium path of the structure. Highlights: Comprehensive ductile-damage model developed for truss structures. Continuum damage model accumulates damage in terms of porosity. Damage accumulates continuously until the theoretical critical value is reached. Excellent fit to stress–strain curves of eight different materials. Modeling of structural concrete better than Mazar's and Lee & Fenves models.